2019
DOI: 10.3892/or.2019.6964
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of exogenous wild‑type p53 mediates the regulation of oncoprotein�18/stathmin signaling via nuclear factor‑κB in non‑small cell lung cancer NCI‑H1299 cells

Abstract: Our previous studies demonstrated that high expression of oncoprotein 18 (Op18)/stathmin promotes malignant transformation of non-small cell lung cancer NCI-H1299 cells. Investigation of the cellular settings determined that NCI-H1299 cells were genetically p53 deficient. In order to determine whether p53 deficiency is associated with Op18/stathmin-mediated high levels of malignancy, exogenous wild-type p53 (p53 wt) was introduced into NCI-H1299 cells in the present study to observe Op18/stathmin signaling cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Several studies have verified that stathmin1 transcription was regulated by wild type and mutant p53 [ 23 , 24 ]. Two SNPs identified in the canine stathmin1 promoter region could affect transcription factor binding [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have verified that stathmin1 transcription was regulated by wild type and mutant p53 [ 23 , 24 ]. Two SNPs identified in the canine stathmin1 promoter region could affect transcription factor binding [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between the AKT and p53 pathways is vital in modulating the cellular response to stress and DNA damage. In conditions where AKT is highly active, it can suppress the pro-apoptotic functions of p53, promoting cell survival ( Chen et al, 2019 ; Han et al, 2019 ).…”
Section: Overview Of Pi3k/akt Signalingmentioning
confidence: 99%
“…Some studies have shown that some mRNA molecules are related to the progress of patients with LUAD ( Chen et al, 2019 ). Dong et al (2021) found that ZLC5 was up-regulated in lung cancer patients, and its high expression predicted a shorter overall survival ( p = 0.007), and as an independent prognostic marker of lung cancer, HR = 2.892; 95% ( Yang et al, 2021 ) CI: 1.297–6.449; p = 0.009; Zhang et al (2019) found that nine mRNA genes ( HMMR, B4GALT1, SLC16A3, ANGPTL4, EXT1, GPC1, RBCK1, SOD1 and AGRN ) were associated with the overall survival rate of lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%